Effects of the economic crisis on entrepreneurship in social economy companies in Spain: a spatial analysis - Santiago Cantarero (AECOOP Escuela de Estudios Cooperativos, 2017)
In recent years, the unfavorable evolution of the economic situation has provoked intense structural and spatial changes in the creation of companies that question the validity of some basic assumptions about entrepreneurial dynamics and territorial development. Therefore, the objective of this paper is to analyze the existence of spatial patterns of creation of social economy  enterprises in Spain and to study their temporal evolution during two stages of intense changes: one of growth (2002-2007) and another of deep generalized crisis (2008-2013). Based on the definition of a cluster index of social economy companies we apply statistical techniques based on spatial econometrics (Moran and LISA index). For this purpose, longitudinal data were taken from the number of companies created in Spain, during the period 2002-2013, under the formulas of social and mercantile economy, comparing later to the autonomic level. Its dynamics are analyzed together with regional GDP as an indicator of the economic context. The more general results indicate that the pattern of expansion of entrepreneurial dynamics in social economy enterprises is negative and regionally heterogeneous, showing the existence of some spatial concentrations in what could be called Clusters of Social Economy Companies. In view of these results and patterns, an erosion in the influence of certain contextual factors (tradition, culture and regulation) on this entrepreneurial activity is evident. Our contributions have implications for academia and policy makers in support of business start-ups and the social economy.